TIPT: The Tracer Injection Planning Tool. (October 2022) - González-Pinzón, Ricardo; Dorley, Jancoba; Singley, Joel; Singha, Kamini; Gooseff, Michael; Covino, Tim
Abstract: Despite their frequent use, there are few simple and readily accessible tools to help guide the logistical planning of tracer injections in streams and rivers. We combined the widely used advection-dispersion-reaction equation, peak concentration estimates based on a meta-analysis of hundreds of tracer injections carried out in streams and rivers, and simple mass balances in a dynamic Excel Workbook to 1) help users decide how much tracer mass should be added to achieve a specific dynamic concentration range that reduces known issues associated with breakthrough curve tail truncation, and 2) generate tables and graphs that can be readily used to plan the deployment of resources. Our Tracer Injection Planning Tool, TIPT, handles instantaneous and continuous tracer injections and assumes steady-state and uniform flow conditions, as well as first-order decay or production. While those assumptions do not strictly apply to natural streams and rivers, they help simplify the planning of tracer injections with a predictive ability that is disproportionally favorable with respect to the few inputs required. TIPT is a versatile, user-friendly, and graphical tool that can help design tracer injections and solute transport experiments that are more easily replicated within and across sites. Thus, TIPT contributes directly to advancing Integrated, Coordinated, Open, and Networked (ICON) principles. Similarly, TIPT can help generate datasets that more closely follow Findable, Accessible, Interoperable, and Reusable (FAIR) principles. We demonstrate the use of TIPT through two case studies featuring 1) a continuous injection in a 2nd order stream and 2) an instantaneous injection in a 7th order stream. Highlights: TIPT can be used to plan instantaneous and continuous tracer injections. TIPT help users decide tracer masses, mixing volumes, and sampling distances. TIPT can be readily used to plan the deployment of human resources and equipment.